The feline mask in "The Gatomachy" - Xouplidis, Panagiotis (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The article offers a comparative approach to Lope de Vega´s mock epic TheGatomachy and the adaptation to the dramatic genre of this masterpiece by Pedro Villora and Jose Padillafor the homonymous theatrical representation of the company La Ensemble, directed by Goyo Pastor,in the Circle of Fine Arts of Madrid in 2009.The mock epic poetry emerges withBatrachomyomachia,a Greek classical poem, attributed falsely to Homer, with strong links to the Aesopic fable.The concept of zoomachia, battle between anthropomorphic animals, introduces an allegory in verse that imitates the epic poetry in a burlesque and critical way. The most famous example of this genre in Spanish literature is Lope de Vega’s TheGatomachy(1634). In this non dramatic poetic work the protagonists are anthropomorphic cats,while in the comedy by Víllora and Padilla appear humans behind feline masks engaged in a battle to the death for love in the magic stage of the Spanish Golden Age. Since the beginningsof the Greek theatre,masks constitute a fundamental visual elementfor being full of symbolisms as they represent the main characteristics of the dramatic characters. Additionally, zoomorphic masks are symbolic references to masked humans disguised as animals in the Dionysian rituals. The Hellenic tradition in Spanish literature through an historic and artistic process confirms in The Gatomachy by Víllora and Padilla the convergence of two genres of the Ancient Greek world: the mock epic poetry and the theatre. The article examines textual and scenic aspects to focus on the transformation of the non dramatic mock epic poetry of the most prestigious representative of the Spanish Golden Age Theater to a modern day play. On the modern theatrical stages cat masks mark the return to the Greek origins of the dramatic art.
Keywords: cat; mask; character; mok epic; comedy